Healthy School Environment Technology Through Biopore Construction in Bandung Regency - Retno Anisa Larasati; Inal Kahfi (Indonesian Journal of Community Empowerment (IJCE), 2026)
This community service program aims to increase environmental awareness in the Bandung Regency community through the creation of biopore holes. Through outreach and education, the community, namely teachers and students, are educated about the importance of biopore holes in maintaining soil quality and preventing flooding. This activity is also related to the stunting prevention program and addresses other social issues such as bullying in local schools. The participatory method used directly involves the community, namely teachers and students, increasing their involvement and awareness of environmental issues. The results of the biopore hole creation are students showing great enthusiasm for caring for their surrounding environment both in the school environment and in their neighborhoods and demonstrating increased community knowledge about environmental management and the positive impact of biopore holes on soil health. This activity is expected to contribute as an exemplary model that may inform and guide the development of similar initiatives in comparable institutional or community contexts regencies to increase environmental awareness and sustainable natural resource management.